The impact of adverse childhood experiences on mental health, sexual risk behaviors, and alcohol consumption in adulthood - Landa-Blanco, Miguel; Vásquez, Gabriela; Portillo, Gretel; Sproviero, Federico; Echenique, Yarani (Frontiers in Psychiatry, 2024)
The purpose of the study was to determine how Adverse Childhood Experiences (ACE) relate to adulthood flourishing, symptoms of depression, anxiety, somatization, self-reported health, sexual risk behaviors, and alcohol consumption. A quantitative cross-sectional methodology was used. A total of 452 adults completed the survey. The most prevalent ACE include physical abuse (44.69%), separation/divorce of parents (41.81%), living with someone with alcohol problems (39.38%), and being sworn, insulted, or humiliated by adults at home (35.62%). Almost one out of every four respondents (24.34%) reported being touched by an adult, 17.92% reported that an adult tried to manipulate the respondent into touching them, and 8.19% were forced to have sexual intercourse. Results indicate that women reported a higher number of ACE than men. The number of ACE is inversely related to flourishing and self-reported health; while being positively associated with participant's scores in depression, anxiety, somatization, sexual risk behaviors, and alcohol use. The regression model, including the eleven ACE and respondents' sex and age, achieved medium effect sizes for somatization, depression, and anxiety symptoms and small effect sizes for flourishing, self-reported health, sexual risk behaviors, and alcohol consumption. Specific ACE have a particularly significant negative impact on mental health outcomes: forced intercourse, witnessing familial violence, verbal humiliation, and living with individuals struggling with mental health issues and drug consumption or who were incarcerated. In conclusion, the study highlights the alarming prevalence of ACE among the Honduran population and their significant negative impact on mental health outcomes during adulthood.